Content analysis of UK newspaper and online news representations of women's and men's 'binge' drinking: a challenge for communicating evidence-based messages about single-episodic drinking?. Issue 12 (27th December 2016) - Patterson, C; Emslie, C; Mason, O; Fergie, G; Hilton, S
Abstract : Objectives: In the UK, men's alcohol-related morbidity and mortality still greatly exceeds women's, despite an increase in women's alcohol consumption in recent decades. New UK alcohol guidelines introduce gender-neutral low-risk alcohol consumption guidance. This study explores how UK newspaper and online news represent women's and men's 'binge' drinking to identify opportunities to better align reporting of harmful drinking with evidence. Design: Quantitative and qualitative content analysis of 308 articles published in 7 UK national newspapers and the BBC News website between 1 January 2012 and 31 December 2013. Results: Articles associated women with 'binge' drinking more frequently than men, and presented women's drinking as more problematic. Men were more frequently characterised as violent or disorderly, while women were characterised as out of control, putting themselves in danger, harming their physical appearance and burdening men. Descriptions of female 'binge' drinkers' clothing and appearance were typically moralistic. Conclusions: The UK news media's disproportionate focus on women's 'binge' drinking is at odds with epidemiological evidence, may reproduce harmful gender stereotypes and may obstruct public understandings of the gender-neutral weekly consumption limits in newly proposed alcohol guidelines. In order to better align reporting of harmful drinking with current evidence, public health advocates may engage with the media with a view to shifting media framing of 'binge' drinking away from specific groups (young people; women) and contexts (public drinking) and towards the health risks of specific drinking behaviours, which affect all groups regardless of context.